Antineutrino Flux from the Laguna Verde Nuclear Power Plant - Marisol Chavez-Estrada; Alexis A. Aguilar-Arevalo (Advances in High Energy Physics)
We present a calculation of the antineutrino flux produced by the reactors at the Laguna Verde Nuclear Power Plant in México, based on the antineutrino spectra produced in the decay chains of the fission fragments of the main isotopes in the reactor core, and their fission rates, which have been calculated using the DRAGON simulation code. We also present an estimate of the number of expected events in a detector made of plastic scintillator with a mass of 1 ton, at 100 m from the reactor cores.